2018
DOI: 10.5001/omj.2018.37
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder and Parental Factors in School Children Aged Nine to Ten Years in Muscat, Oman

Abstract: This was the first study that examined familial and parental characteristics of children with ADHD as potential risk factors for the condition. Such psychosocial factors could be employed to further the development of more proficient preventative measures and remedial services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“… 14 Specifically, our study found a lower prevalence of ADHD (4.6%) as compared to findings from other countries, notably; 6.3% in Kenya, 24 5.91% in China, 25 and 8.7% in the United States of America. 19 However, the ADHD prevalence in our study population was similar to estimates in Saudi Arabia, 26 and Oman population, 27 and a recent meta-analysis with 3.4% (95% CI 2.6–4.5) in children, 28 in addition to significantly higher than that in Malaysia school-age children with only 1.61% ADHD prevalence. 29 These variations can be explained by the diversity of measurement tools and geographical, cultural characteristics between countries.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 14 Specifically, our study found a lower prevalence of ADHD (4.6%) as compared to findings from other countries, notably; 6.3% in Kenya, 24 5.91% in China, 25 and 8.7% in the United States of America. 19 However, the ADHD prevalence in our study population was similar to estimates in Saudi Arabia, 26 and Oman population, 27 and a recent meta-analysis with 3.4% (95% CI 2.6–4.5) in children, 28 in addition to significantly higher than that in Malaysia school-age children with only 1.61% ADHD prevalence. 29 These variations can be explained by the diversity of measurement tools and geographical, cultural characteristics between countries.…”
Section: Discussionsupporting
confidence: 86%
“…Differences in methodology may also explain the variations in the reported rate, typically the present study covered only children aged 6 to 7 years instead of pupils at all grades of primary school like in other studies. 19,[24][25][26][27]29 In Vietnam, few studies have analyzed data on ADHD rate, in which one earlier study carried out among primary school pupils in Mekong River Delta identified that an ADHD prevalence among primary schools (grades 1-5) with 7.7% was higher than our estimate. 14 This disparity is assumed to be caused by the differences in study methodology and the improvement of mental health among pregnant women in Hue City, where the rate of maternal depression was found to be lower than in other cities in the North and South of Vietnam.…”
Section: Discussioncontrasting
confidence: 77%
“…A previous study conducted in Oman suggested that the prevalence rate of ADHD was 8.8% among 9-10-yearolds. 25 However, it is not clear what percentage of this population also had OSA. In the current study, although there was a significant decrease in mean inattention and hyperactivity scores post-AT, this change does not indicate a reversal of ADHD-like symptoms, as the mean post-AT score remained above the cut-off value of >15 on the CTRS scale.…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, although there was a significant decrease in mean inattention and hyperactivity scores post-AT, this change does not indicate a reversal of ADHD-like symptoms, as the mean post-AT score remained above the cut-off value of >15 on the CTRS scale. 25 Longer-term evaluation would perhaps shed more light on this finding.…”
Section: Discussionmentioning
confidence: 98%
“…The current systematic review included 33 studies ( Table 1 ) [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , 45 , 55 , 56 , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [77] , [78] , [79] , [80] ].…”
Section: Resultsmentioning
confidence: 99%